AI-Driven Autonomous Treasury Orchestration: A Next-Generation Framework for Global Liquidity Optimization - Nirajkumar Radhasharan Barot (International Journal of Computational and Experimental Science and Engineering, 2025)
This article presents an overall framework for AI-enabled autonomous treasury orchestration, transforming traditional rules-based cash management into an intelligent, self-optimizing system capable of making real-time decisions across global liquidity operations. It combines four core technological pillars: reinforcement learning algorithms for dynamic investment allocation, predictive cash flow modeling using advanced time-series architectures, adaptive risk management systems that react to market conditions and evolving counterparty profiles, and explainable AI mechanisms that ensure regulatory compliance and auditability. Traditional Treasury Management Systems execute on hardwired decision trees, which cannot adapt to the emergence of turbulent market conditions, unexpected cash flow disruptions, or changing risk profiles. Large pieces of potential optimization value cannot, therefore, be realized. To address this critical gap, the contribution of this study is to develop an autonomous orchestration architecture that enables AI agents to continuously learn from historical patterns and predict future liquidity needs with increased accuracy, while executing allocation strategies that balance the competing objectives of yield maximization, risk minimization, and liquidity preservation. The multi-agent system design within the framework enables specialized agents for prediction, optimization, execution, and monitoring to cooperate towards unified organizational goals, with robustly designed governance controls and human oversight mechanisms. Validation through simulation environments and backtesting frameworks reflects that AI-augmented approaches achieve superior risk-adjusted performance compared to static rule-based systems. Contributing valuable implementation guidance for financial institutions pursuing digital transformation of treasury operations, the article addresses the challenges of integrating with legacy systems, regulatory compliance requirements, and issues related to organizational change management that are crucial for the successful deployment of autonomous treasury technologies.